Astragaloside IV inhibits ventricular remodeling and improves fatty acid utilization in rats with chronic heart failure. Issue 3 (22nd May 2018) - Tang, Bin; Zhang, Jin-Guo; Tan, Hong-Yong; Wei, Xi-Qing
Abstract : Chronic heart failure (CHF) is the end-stage of many cardiovascular diseases and severely affects the patients' lifespan. Inhibiting ventricular remodeling is thus a primary treatment target for CHF patients. Astragaloside IV (AS-IV) can improve cardiac function and protect myocardial cells. The study aims to investigate the effects of AS-IV on ventricular remodeling and explore its role in regulating energy metabolism using a rat CHF model. Sprague–Dawley rats were divided into five groups ( n =20 per group): CHF + benazepril hydrochloride (Benazepril HCL), CHF + low-dose (30 mg.kg −1 .day −1 ) AS-IV, CHF + high-dose (60 mg.kg −1 .day −1 ) AS-IV, and a sham control group. After 8 weeks of treatment, the cardiac structure and functional parameters were measured. Morphological changes in the myocardial tissue in five groups were evaluated. Protein and mRNA expression of peroxisome proliferator-activated receptor α (PPARα), medium-chain acyl-CoA dehydrogenase (MCAD), and muscle carnitine palmitoyl transferase-1 (MCPT1) were also analyzed. Our results showed that the left ventricular mass index (LVMI), collagen volume fraction (CVF), and free fatty acid (FFA) concentration of CHF group rats increased when compared with sham control group, while the protein and mRNA expressions of PPARα, MCAD, and MCPT1 decreased in CHF. Importantly, treatment with AS-IV (CHF + AS-IV group) showed improved heart function and structure, increased expression of PPARα, MCAD, and MCPT1 and improved FFA utilization in comparison with CHF group. In conclusion, our study shows that AS-IV inhibits ventricular remodeling, improves cardiac function, and decreases FFA concentration of CHF model rats. Our findings suggest a therapeutic potential of using AS-IV in CHF.